2009
DOI: 10.1111/j.1463-5224.2009.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural assessment of retinal sheet allograft transplantation in feline hereditary retinal degeneration

Abstract: Fetal sheet transplants can integrate well within a degenerating cat retina and develop good lamination of photoreceptors. Functional improvement was not demonstrated by ERG in cats with well-laminated grafts. Transplants need to be further evaluated in cat host retinas with a more advanced retinal degeneration using longer follow-up times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…However, it was revealed that the clonogenic spheres derived from the mouse and human CE originate from differentiated pigmented CE cells rather than the stem cell population harbored in the CE [5]. Fetal cat retinal sheets incubated with BDNF microspheres were transplanted to the subretinal space to investigate whether it is possible for sheets of fetal retinal allograft to integrate into the dystrophic Abyssinian cat retina where progressive rod cone degeneration is taking place [6]. To the authors knowledge there is a lack of information regarding generation, proliferation, and differentiation of progenitor cells during embryonic and fetal stages in other mammals, particularly in the dog where progressive retinal degeneration associated with different ocular diseases is frequently observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was revealed that the clonogenic spheres derived from the mouse and human CE originate from differentiated pigmented CE cells rather than the stem cell population harbored in the CE [5]. Fetal cat retinal sheets incubated with BDNF microspheres were transplanted to the subretinal space to investigate whether it is possible for sheets of fetal retinal allograft to integrate into the dystrophic Abyssinian cat retina where progressive rod cone degeneration is taking place [6]. To the authors knowledge there is a lack of information regarding generation, proliferation, and differentiation of progenitor cells during embryonic and fetal stages in other mammals, particularly in the dog where progressive retinal degeneration associated with different ocular diseases is frequently observed.…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation of full-thickness retina has been reported in several animal models previously [68,14]. In earlier work in pig and rabbit eyes, we used a siliconized glass cannula for transplantation in which the elastic retinal graft adopted a rolled-up shape.…”
Section: Discussionmentioning
confidence: 99%
“…To improve graft survival and organization, transplantation of non-disrupted tissue in the form of full-thickness retina has been explored by a few groups [58]. The rationale of the full-thickness paradigm is to limit antigen exposure to the host immune system, and retain the laminated organization of the donor retina with its delicate intrinsic microcircuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Other therapy approaches for which the CEP290-mutant cat has been used include the following: transplantation of sheets of allogenic fetal retinal tissue [21], and of brain derived neural precursor cells [22] into the subretinal space. In the latter study retinal incorporation of some of the injected cells was detected.…”
Section: Cep290-mutant Catmentioning
confidence: 99%